Foot-trembling behavior in Semipalmated Plover Charadrius semipalmatus reveals prey on surface of Brazilian beaches - Cestari, César [UNESP] (Instituto Virtual da Biodiversidade (BIOTA/FAPESP), 2009)
O tremular dos pés é um comportamento de forrageio utilizado por batuíras e quero-queros que maximiza a exposição de presas e por conseqüência, pode aumentar o sucesso de captura. Apesar disso, nenhuma descrição detalhada desta técnica está disponível para batuíra-de-bando Charadrius semipalmatus. No presente estudo, eu descrevo o comportamento de tremular dos pés da espécie durante sua estadia temporária em praias na região sudeste do Brasil.

Foot-trembling is a foraging technique normally performed by plovers and lapwings. It exposes preys, and may increase the likelihood of capture. Currently, no detailed description of this technique is available for the Semipalmated Plover Charadrius semipalmatus. This article described the foot-trembling behavior during wintering of this species in southeastern Brazilian beaches.
Tremular dos pés da batuíra-de-bando Charadrius semipalmatus: revelando presas na superfície de praias brasileiras
Keywords: comportamento de forrageio; tremular dos pés; batuíra-de-bando; ave costeira; sudeste do Brasil; foraging behavior; foot-trembling; Semipalmated Plover; shorebird; southeastern Brazil